Identification of Lama glama as Reservoirs for Acinetobacter lwoffii - Ledesma, Martín M.; Díaz, Ailén M.; Barberis, Claudia; Vay, Carlos; Manghi, Marcela A.; Leoni, Juliana; Castro, Marisa S.; Ferrari, Alejandro (Frontiers in Microbiology, 2017)
South American Camelids have an increasing relevance in local economies, worldwide. These animals are bred for their meat, fur and as companion and therapy animals. Thus, their sanitary status should be well established. According to the OIE (World Organization for Animal Health), respiratory infections mainly produced by Pasteurella spp have been reported for camelids. It has been stated that this microorganism causes a mild disease, although many authors report it is an important cause of mortality among alpacas. Nevertheless, the incidence of infection by Pasteurella spp in camelids still needs to be investigated. The aim of the present study was to analyze the occurrence of nasopharyngeal colonization of Lama glama by respiratory bacteria, and to assess the usefulness of serological tests for clinical diagnosis. The colonization was studied by culture techniques carried out with material taken by nasopharyngeal swabs. Bacterial isolates were first phenotypically characterized and then identified by MALDI/TOF-MS. The presence of specific serum antibodies was studied by ELISA and Western blot. In the present work Pasteurella spp was not found. Nevertheless, we report for the first time, the colonization of Lama glama by bacteria of the Acinetobacter lwofii, at a reliable level in 19.4% of the animals. Acinetobacter species are found in different environmental sources, as well as vegetables, animals, and humans, and their role in infections has recently gained relevance. The results presented herein contribute to a better understanding of the respiratory microbiota in camelids, and increase the knowledge about environmental distribution of Acinetobacter non-baumanii species. Given that these respiratory bacteria might be the cause of infection among cattle, and even humans, this report highlights the need for further research.